2012
DOI: 10.1007/s13224-012-0280-3
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility Pattern of Various Azoles Against Candida Species Causing Vulvovaginal Candidiasis

Abstract: In the current study, prevalence rate of VVC was found to be 18.4 %, and among the various azoles tested, fluconazole has the highest antimicrobial activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…Figure 1 summarizes the distribution of Candida species isolated from vaginal swabs from population-based studies conducted in different countries including our study over the last decade. China, Brazil, Tunis, Kuwait, India, Greece and Turkey have reported that C.albicans remains the most commonly isolated yeast (60%-80%) in women diagnosed with VVC [21][22][23][24][25][26][27]. On the other hand, an increasing trend in the occurrence of NCAC (58%-60%) over time has also been observed in Pakistan and Burkina Faso [28,29].…”
Section: Resultsmentioning
confidence: 98%
“…Figure 1 summarizes the distribution of Candida species isolated from vaginal swabs from population-based studies conducted in different countries including our study over the last decade. China, Brazil, Tunis, Kuwait, India, Greece and Turkey have reported that C.albicans remains the most commonly isolated yeast (60%-80%) in women diagnosed with VVC [21][22][23][24][25][26][27]. On the other hand, an increasing trend in the occurrence of NCAC (58%-60%) over time has also been observed in Pakistan and Burkina Faso [28,29].…”
Section: Resultsmentioning
confidence: 98%
“…identified in women with VVC and depends largely on the location as well as the population studied (Figure 1). Recent studies from countries such as China, Brazil, Tunis, Kuwait, India and Turkey have reported that C. albicans remains the most commonly isolated yeast (60%-80%) in women diagnosed with VVC [38][39][40][41][42][43]. On the other hand, an increasing trend in the occurrence of NCAS (58%-60%) over time has also been observed in Pakistan and Burkina Faso [31,44].…”
Section: Discussionmentioning
confidence: 99%
“…Azoles are fungistatic, thus inhibiting the growth of fungi leading to a clearance of the infection. Most C. albicans strains are susceptible to available antimycotic drugs and real resistance of isolates is rare [42][43][44][45]. Topical azole agents are available in a variety of formulations and are often sold over the counter for self-treatment.…”
Section: Candida Albicansmentioning
confidence: 99%